Identification of novel multi-stage histone deacetylase (HDAC) inhibitors that impair Schistosoma mansoni viability and egg production - Alessandra Guidi; Fulvio Saccoccia; Nadia Gennari; Roberto Gimmelli; Emanuela Nizi; Cristiana Lalli; Giacomo Paonessa; Giuliana Papoff; Alberto Bresciani; Giovina Ruberti (Parasites & Vectors, 2018)
Abstract Background Novel anti-schistosomal multi-stage drugs are needed because only a single drug, praziquantel, is available for the treatment of schistosomiasis and is poorly effective on larval and juvenile stages of the parasite. Schistosomes have a complex life-cycle and multiple developmental stages in the intermediate and definitive hosts. Acetylation and deacetylation of histones play pivotal roles in chromatin structure and in the regulation of transcription in eukaryotic cells. Histone deacetylase (HDAC) inhibitors modulate acetylation of several other proteins localized both in the nucleus and in the cytoplasm and therefore impact on many signaling networks and biological processes. Histone post-translational modifications may provide parasites with the ability to readily adapt to changes in gene expression required for their development and adaptation to the host environment. The aim of the present study was to screen a HDAC class I inhibitor library in order to identify and characterize novel multi-stage hit compounds. Methods We used a high-throughput assay based on the quantitation of ATP in the Schistosoma mansoni larval stage (schistosomula) and screened a library of 1500 class I HDAC inhibitors. Subsequently, a few hits were selected and further characterized by viability assays and phenotypic analyses on adult parasites by carmine red and confocal microscopy. Results Three compounds (SmI-124, SmI-148 and SmI-558) that had an effect on the viability of both the schistosomula larval stage and the adult worm were identified. Treatment with sub-lethal doses of SmI-148 and SmI-558 also decreased egg production. Moreover, treatment of adult parasites with SmI-148, and to a lesser extent Sm-124, was associated with histone hyperacetylation. Finally, SmI-148 and SmI-558 treatments of worm pairs caused a phenotype characterized by defects in the parasite reproductive system, with peculiar features in the ovary. In addition, SmI-558 induced oocyte- and vitelline cell-engulfment and signs of degeneration in the uterus and/or oviduct. Conclusions We report the screening of a small HDAC inhibitor library and the identification of three novel compounds which impair viability of the S. mansoni larval stage and adult pairs. These compounds are useful tools for studying deacetylase activity during parasite development and for interfering with egg production. Characterization of their specificity for selected S. mansoni versus human HDAC could provide insights that can be used in optimization and compound design.